Perioperative Outcomes of Open Extra-peritoneal Versus Laparoscopic Radical Cystoprostatectomy: A single Center Comparative Study - çanakcı, cengiz; özkaptan, Orkunt; dinçer, Erdinç; Ipek, Osman Murat; Dalgıç, Gürkan; Sahan, Ahmet (Urology Journal, 2024)
Purpose: To compare 90-day perioperative complications and pathological outcomes between laparoscopic radical cystectomy (LRC) and extraperitoneal radical cystectomy (EORC) approaches. Materials and Methods: All operations were performed in a single high-volume tertiary referee center by the same surgical team.Males ≥ 18 years with pre-cystectomy clinical T1–T3 disease and having undergone an ileal conduit were included. Exclusion criteria included patients with inflammatory bowel disease, previous pelvic and/or abdominal irradiation, neo-adjuvant chemotherapy, and/or clinical T4 disease. Perioperative outcomes such as operative time, estimated blood loss, transfusion rate, hospital stay, and 90-day complications were evaluated. The recovery duration of regular bowel activity, mean stool passage,and ileus rates were recorded. Results: A total of 221 patients met the inclusion criteria(81 LRC and 130 EORC). Demographics and preoperative parameters were comparable. Intraoperative estimated blood lossfavored LRC by a median of 450 mL (200-900) P=.021) vs. a median of 700 mL (300-2900) for EORC. The transfusion rate did not differ between the two groups; %14.8 (N=12) for the LRC and %20.8 (N=27) for EORC (P=.37). The median hospital stay was 9 (4-49) days for EORC and 8 (4-29) days for LRC (P=.011). The need for analgesics to control pain through an epidural catheter was higher for EORC (P=.042). There was no difference in overall complication rates (P=.47). Conclusion: Although LRC appears to have a slight advantage over EORC, both techniques yield satisfactory results in regard to ileus rates and 90-day perioperative complications.